Photoprotection against the UVB-induced oxidative stress and epidermal damage in mice using leaves of three different varieties of Lepidium meyenii (maca) - Gonzales Castañeda, Cynthia (2011)
Background Skin exposure to ultraviolet (UV) B radiation leads to epidermal damage and generation of reactive oxygen species. The photoprotective effect of extracts of three varieties of leaves (red, yellow, and black) from maca (Lepidium meyenii), a plant from the Peruvian highlands, was assessed in mouse skin exposed to UVB radiation. Materials and methods The hydroalcoholic extracts of three varieties of maca leaves were applied topically to the dorsal skin of young-adult male mice prior to exposition to UVB radiation. Results The three varieties had UVA/UVB absorptive properties and presented antioxidant activity, being highest with red maca, followed by black and yellow maca. The three varieties of maca leaves prevented the development of sunburn cells, epidermal hyperplasia, leukocytic infiltration, and other alterations produced by UVB radiation. Mice treated with black maca showed the highest superoxide dismutase levels, and mice treated with black and yellow maca showed higher catalase levels in skin, whereas red maca protected the skin and liver against significant increases in the lipid peroxidation activity observed in the unprotected animals. Conclusion The presence of significant antioxidant activity and the inhibition of lipid peroxidation suggest that the observed protection could be partly attributable to this mechanism. © 2011 The International Society of Dermatology.